The Effect of Corporate Social Responsibility on Earnings Management: Evidence from Chinese Manufacturing Industry - Li, Jia-Ru (2022)
Chinese firms need to face increasing issues about corporate social responsibility (CSR). And due to rising economic impact from Chinese firms, global investors may suffer from scandals like earnings management (EM) and other irresponsible corporate behaviors, paying more attention to firms’ CSR and EM. This paper investigates how CSR is associated with EM. Inspired by the findings that CSR affects EM differently in various industries (Yip, Van Staden and Cahan, 2011), this paper selects Chinese listed manufacturing firms as samples and collect their data from 2013 to 2019 in order to examine how CSR affect firms’ earnings smoothing and earnings aggressiveness.